Accounting Practitioners Perception over the Impact of IFRS Implementation on the Performance of Entities in the Construction Sector from the Western Region of Romania - Bogdan, Oana; Mateș, Dorel; Domil, Aura Emanuela; Pușcaș, Marina Adriana; Pușcaș, Ancuța; Teșu, Ramona (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
Through this paper, we want to identify the correlations between the benefits and costs of adopting IFRS standards in construction entities in the Western Region of Romania and their performance, using the Pearson correlation coefficient, which measures and describes the direction, degree and form of the association between two variables, thus obtaining high, reasonable, weak and very weak links between the benefits / costs and the performance of the entity. The tool used in the research undertaken by construction companies is the questionnaire. The questionnaire "On the Costs and Benefits of IFRS in Construction Companies in the Western Region of Romania" was disseminated among professional accountants in order to identify the perceptions of economists operating in construction companies in the Western Region Romania on the costs and benefits of implementing international standards. Thus, through this paper we aim to identify the correlations between the following benefits and costs: - Benefits of implementation: comparability of information, increased transparency, increased access to capital, cost savings, reduction of informational asymmetry, - Implementation costs: IFRS readiness level, complexity of standards, link between accounting and taxation, existing accounting tradition, costs associated with IFRS conversion, and - Performance of the entity viewed from the perspective of: total revenue and turnover. In the research, we chose to present the analysis of compared to both the total revenues and the turnover, because the difference between the two economic-fiscal indicators is mainly represented by the financial revenues and the incomes from the disposals of assets.